2014
DOI: 10.1007/s00394-014-0759-z
|View full text |Cite
|
Sign up to set email alerts
|

A mid-morning snack of almonds generates satiety and appropriate adjustment of subsequent food intake in healthy women

Abstract: PurposeTo assess the effect of consuming a mid-morning almond snack (28 and 42 g) tested against a negative control of no almonds on acute satiety responses.MethodOn three test days, 32 healthy females consumed a standard breakfast followed by 0, 28 or 42 g of almonds as a mid-morning snack and then ad libitum meals at lunch and dinner. The effect of the almond snacks on satiety was assessed by measuring energy intake (kcal) at the two ad libitum meals and subjective appetite ratings (visual analogue scales) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 23 publications
3
56
0
Order By: Relevance
“…Our results are consistent with those of Cioffi et al Considering the results and the timing of evaluation in this study, we conclude that beverages containing 30 g of plant protein or 11 g of soluble fiber may have the potential to control cravings and hunger feelings if consumed at mid-morning. This observation is consistent with the results obtained by Hull et al, (2015) in which subjects consuming a snack high in protein and fiber felt full for a longer period and had reduced hunger when consumed at mid-morning prior to an ad libitum meal [38].…”
Section: Ad Libitum Lunchsupporting
confidence: 93%
“…Our results are consistent with those of Cioffi et al Considering the results and the timing of evaluation in this study, we conclude that beverages containing 30 g of plant protein or 11 g of soluble fiber may have the potential to control cravings and hunger feelings if consumed at mid-morning. This observation is consistent with the results obtained by Hull et al, (2015) in which subjects consuming a snack high in protein and fiber felt full for a longer period and had reduced hunger when consumed at mid-morning prior to an ad libitum meal [38].…”
Section: Ad Libitum Lunchsupporting
confidence: 93%
“…Further studies should assess if this finding is associated with a more pronounced satiety feeling after almond ingestion, as compared with other meals containing a similar amount of nutrients. Previous studies found effects of almonds on fullness and hunger levels [63,64], an acute satiating effect of almond ingestion, and a dose-dependent enhanced satiety following an almond snack in the midmorning [65]. Furthermore, a recent study showed comparable postprandial hunger, desire to eat, fullness, and neural responses to visual food stimuli after the ingestion of almonds or baked food, linking these results with energy and macronutrient contents [66].…”
Section: Discussionmentioning
confidence: 85%
“…Previously, almonds were mostly added to foods such as, e.g., cereals and muffins (24,31), whereas we recommended that almonds be eaten on an empty stomach (early in the morning, before breakfast). A number of recent studies have also recommended the preferential use of almonds as snacks (40), on an empty stomach (41,42).…”
Section: Discussionmentioning
confidence: 98%